1992
DOI: 10.1107/s0021889892004096
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction investigations of CaF2 at high pressure

Abstract: Synchrotron-radiation X-ray diffraction studies of CaF2 at high pressures have been performed on a powder sample up to 45 GPa and on a single-crystal sample up to 9.4 GPa. The bulk modulus of the low-pressure phase was determined to be B o = 87 (5) GPa. A phase transition was observed at about 9.5 GPa. The transition is accompanied by a volume contraction of 11%. The high-pressure phase is orthorhombic PbC12 type (space group Pbnm). The sample only partially reverts to the low-pressure phase upon release of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 9 publications
(11 reference statements)
8
78
1
2
Order By: Relevance
“…Our average precisions in volume for the two materials (1 part in 12 500 for fluorite, 1 part in 9000 for quartz) yield much closer precisions in pressure, with quartz being marginally better for pressure determination at lower pressures and marginally worse than fluorite at 9 GPa. Thus, quartz is more suited to pressure measurement at low pressures and, of course, can be used at pressures in excess of the limit of 9.2 GPa at which fluorite undergoes a phase transition which is destructive of single crystals (Gerward et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Our average precisions in volume for the two materials (1 part in 12 500 for fluorite, 1 part in 9000 for quartz) yield much closer precisions in pressure, with quartz being marginally better for pressure determination at lower pressures and marginally worse than fluorite at 9 GPa. Thus, quartz is more suited to pressure measurement at low pressures and, of course, can be used at pressures in excess of the limit of 9.2 GPa at which fluorite undergoes a phase transition which is destructive of single crystals (Gerward et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for the antifluorite-anticotunnite phase transition is already well understood because of the numerous well-known pressure-induced fluorite-cotunnite transitions that occur [23,24]. If one pictures the antifluorite structure as (111) planes of anions separated by pairs of (111) planes composed of ions from the cation sublattice, the mechanism for the transition can be seen as a displacement of the anions in the [111] directions, half to the adjacent upper plane and half to the adjacent lower plane, accompanied by rotations and distortions of the Li triangular polyhedra within the planes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[49,51,52,55,57,[61][62][63][64]). Cubic F m3m is known to transform into the orthorhombic P nma phase at a pressure between 8 and 10 GPa, accompanied by an increase of the coordination number of Ca from 8 to 9.…”
Section: A Bulk Propertiesmentioning
confidence: 99%
“…Cubic F m3m is known to transform into the orthorhombic P nma phase at a pressure between 8 and 10 GPa, accompanied by an increase of the coordination number of Ca from 8 to 9. X-ray diffraction and Raman spectroscopy have shown that this high pressure phase is stable up to 49 GPa at room temperature 49,51 . In Fig.…”
Section: A Bulk Propertiesmentioning
confidence: 99%